Logistics management and its relation with the profitability of construction companies in the province of San Román, Puno - Paricahua Laura, Helen Rossi (2022)
Objective: To determine how logistics management is related to the profitability of construction companies in the province of San Román, Puno. Method: The type of study was correlational, witn a non-experimental design and quantitative approach. The sample consisted of 53 construction companies in the province of San Roman. A 33-question survey was used with 5 alternative value responses. Spearman's correlation test was performed between the variable’s logistics management and profitability of construction companies. Results: A high positive correlation was found between the study variables with a significant value of 0.000, which is below the 0.05 degree of significance. Conclusion: Logistics management is directly related to the profitability of construction companies in the province of San Roman since there is a high positive correlation between the two variables. Also, the greater the control in purchasing and inventory management, the greater the profitability.